Antimicrobial activity and phosphorus release behavior of starch/chitosan hydrogel - Phuong, Le Thi; Quyen, Tran Ngoc; Be Thi, Duong Thi; Khoa, Nguyen Cuu (Vietnam Journal of Chemistry, 2014)
Use of slow release fertilizer has become a new trend to improve fertilizer use efficiency and minimize environmental pollution. In this paper, the phosphorus release behavior of controlled-release fertilizer (CRF) hydrogels, which were prepared from starch/chitosan and formaldehyde crosslinker, was investicated. The antimicrobial activities of these membranes were also investigated. The results showed, that these membranes have high activity against E. coli, Aspergillus niger and F. oxysporum. The membranes exhibited capability of encapsulation and slow release of phosphorus fertilizer. Therefore, such membranes can be used to prolong release of fertilizer for long-term plants. Keywords: Slow release fertilizer, hydrogel, chitosan, E. coli.